(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2019)
We have studied pressure induced pseudomelting implied by the negative clapeyron slope for Silicon. Pressure induced amorphization was based primarily on Raman measurements. This does not rule out the possibility of a transformation to a phase which may not have a Raman-active mode such as the primitive hexagonal. Energy dispersive x-ray diffraction measurements on the sample had shown pressure induced annealing of nanocrystalline regions. Since this would have resulted in an increase of the particle size and reduced surface effects, the high pressure behavior should have been similar to that of surface terminated nanoparticles. We have observed that the cubic nano π-silicon undergoes a crystalline-crystalline phase transition to the primitive hexagonal phase under high pressure at 20Gpa and the amorphous phase arised only on release of pressure. This observation is consistent with the transformation seen earlier in the case of surface terminated nanocrystalline silicon. Nanoamorphous phase thus obtained transforms reversibly to the Ph phase under further pressure cycles. The role of particle size in this reversible behavior. Our results showed that the reversible inter conversion also takes place in bulk amorphous Silicon, provided the pressure release is fast, unlike in the case of nanoamorphous Silicon. Our studies showed that irrespective of the method of preparation or size of the amorphous Silicon particles, it always transforms to primitive hexagonal phase under compression. The obtained results were found in good agreement with previously obtained results.